Combustion and heat transfer characteristics inside the combustion chamber of a wood pellet boiler - Ahn, Joon; Kim, Jong Jin (Journal of mechanical science and technology, 2014)
A grate-firing boiler was developed for wood pellet fuel, and then its combustion characteristics were tested. The flame was stretched to the exit of the combustion chamber, implying insufficient space for complete combustion. As a first step to resolve this problem, a numerical simulation was conducted for the combustion chamber. Turbulent and chemically reacting flow was considered by implementing a homogeneous reaction model. Flow field from the simulation showed strong recirculation flow at the upstream corner of the chamber, along which the flame was stretched to the exit. Based on these results, we suggest possible modification of the combustion chamber to improve combustion characteristics, such as relocating its exit or installing internals like guide vanes.